Antioxidative enzymes, carbonic anhydrases and claudins in pediatric brain tumors : prognostic and predictive value - Nordfors, Kristiina; Tampere University Press (Acta Universitatis Tamperensis, ISSN 1455-1616, 2011)
Tiivistelmä.
Keywords: aivot; kasvaimet; aivokasvaimet; entsyymit; lapset (ikäryhmät); antioksidantit